Meningkatkan Kemampuan Eksplorasi Gerak Tari Dengan Metode Karya Wisata Pada Siswa Remaja Sanggar Tari Sekar Putri di Depok Jawa Barat - Syella Yuliamanesti, Afridha; Kusumawardani, Dwi; Setiawati, Rahmida (Jurnal Pendidikan Tari, 2022)
The students of Sanggar Sekar Putri have not been able to explore dance moves well. This study aims to describe the field trip method's application process to enhance the ability to explore dance moves and improve students' ability to explore dance moves. The study was conducted because the Sanggar Tari Sekar Putri Depok (Sekar Putri Dance Studio in Depok) students' ability to explore dance moves was low. Kemmis' and Mctaggart's action research method, as well as the application of the field trip learning method, was used in this study. This study was conducted in two cycles, with each cycle consisting of four stages: planning, action, observation, and reflection. Observation, interviews, and tests were used as the data collection techniques. The study involved collaborators in assessing and evaluating the field trip method's outcomes to improve the ability to explore dance moves. The results showed that the field trip method's application could improve the teenage students' ability to explore dance moves based on the results of the pre-cycle score of 49.8, with the first cycle increased to 65.9, and the second cycle increased to 81.2.